Mandibular radiomorphometric assessment of bone mineral density in survivors of pediatric hematopoietic stem-cell transplantation - Frascino, Alexandre Viana; Costa, Claudio; Salgado, Daniela Miranda Richarte de Andrade; Coracin, Fabio Luiz; Fava, Marcelo [UNESP]; Odone-Filho, Vicente (Elsevier, 2019)
OBJECTIVE: Hematopoietic stem-cell transplantation (HSCT) childhood survivors of hematologic malignancies are prone to develop late osteopenia and osteoporosis. The purpose of this retrospective study was to quantitatively and qualitatively assess bone mineral density (BMD) in HSCT childhood survivors and to compare the effectiveness of both qualitative and quantitative assessment methods. METHODS: DESIGN BMD assessment using panoramic radiographs of childhood HSCT survivors aged 3.69-18.88 years using two radiomorphometric indexes. Case-control double-blinded comparison of panoramic radiographic images from childhood HSCT survivors and age- and sex-matched healthy controls. Quantitative assessment was performed by measuring the cortical bone width bilaterally at the mental foramen level. Qualitative assessment was performed using the mandibular cortical index bilaterally on all panoramic images. RESULTS: Radiographs were taken 6.59-83.95 months after bone marrow transplantation [median±SD=25.92 ±24.9 months]. Fifty-two panoramic radiographic images were analyzed: 21 from HSCT survivors and 31 from healthy controls aged 3.69-25.1 years [mean±SD=11.89±5.28 years]. The mandibular cortical bone width was 17% smaller in childhood HSCT survivors than in healthy controls (case group: 2.420, control group: 3.307; p=0.00617). Qualitative analysis revealed an increased frequency of severe mandibular cortical erosion in childhood HSCT survivors, although no significant difference was observed (case group: 1.540, control group: 1.490; p=0.32). The interobserver agreement was 85% (Kappa index). CONCLUSIONS: HSCT childhood survivors exhibit quantitative and qualitative mandibular bone impairments. Further studies are needed to establish an association between mandibular cortical bone impairment and osteoporosis.
Keywords: Bone Marrow Transplantation; Children; Hematopoietic Stem Cell Transplantation; Osteoporosis; Radiomorphometric Assessment